2021
DOI: 10.4014/jmb.2106.06031
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_Circ_0001947/MiR-661/DOK7 Axis Restrains Non-Small Cell Lung Cancer Development

Abstract: Hsa_circ_0001947 is associated with multiple cancers, but its function in non-small cell lung cancer (NSCLC) is ambiguous and needs further research. The targeting relationship among circ_0001947, miR-661, and downstream of tyrosine kinase 7 (DOK7) was predicted by database and further verified by dual-luciferase reporter assay, while their expressions in cancer tissues and cells were detected by quantitative real-time polymerase chain reaction (qRT-PCR). After transfection, cell biological behaviors and expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…We further showed that DOK7 serves as a negative regulator of JAK signaling pathway in BLCA cells. In agreement with our data, DOK7 was reported as a tumor suppressor in glioma, breast and lung cancer [19,20,[30][31][32][33]. For example, DOK7 was found to be down-regulated in lung cancer and its reduced expression was associated with the poor survival in lung cancer patients [30][31][32].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We further showed that DOK7 serves as a negative regulator of JAK signaling pathway in BLCA cells. In agreement with our data, DOK7 was reported as a tumor suppressor in glioma, breast and lung cancer [19,20,[30][31][32][33]. For example, DOK7 was found to be down-regulated in lung cancer and its reduced expression was associated with the poor survival in lung cancer patients [30][31][32].…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our data, DOK7 was reported as a tumor suppressor in glioma, breast and lung cancer [19,20,[30][31][32][33]. For example, DOK7 was found to be down-regulated in lung cancer and its reduced expression was associated with the poor survival in lung cancer patients [30][31][32]. In breast cancer, DOK7 suppresses the cell growth and mobility by targeting PI3K/AKT pathway [20].…”
Section: Discussionsupporting
confidence: 89%
“…It has been found that circAFF2 plays different roles in different tumours. For example, circAFF2 was downregulated in non‐small cell lung cancer, 40 and acted as a sponge for miR‐661, inhibiting tumour progression by enhancing the expression of DOK7 40 . In gastric cancer, circAFF2 upregulates ANTXR 1 expression by adsorbing miR‐6894‐5p, thereby promoting tumour proliferation 41 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, circAFF2 was downregulated in non‐small cell lung cancer, 40 and acted as a sponge for miR‐661, inhibiting tumour progression by enhancing the expression of DOK7. 40 In gastric cancer, circAFF2 upregulates ANTXR 1 expression by adsorbing miR‐6894‐5p, thereby promoting tumour proliferation. 41 Additionally, circAFF2 is highly expressed in renal cell carcinoma (RCC), and high expression patients with RCC had a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the dysregulation of circ_0001947 is linked to the development of NSCLC [ 2 ], gastric cancer [ 4 ] and acute myeloid leukemia [ 12 ]. Moreover, Qu et al and Zhi et al demonstrated that circ-AFF2 is highly expressed in RA and aggravated RA-FLS growth, inflammation, invasion and migration via regulating miR-650/CNP axis and miR-375/TAB2 axis [ 23 , 33 ].…”
Section: Discussionmentioning
confidence: 99%